2021
DOI: 10.1038/s41598-021-85409-w
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation restores altered functional connectivity of central poststroke pain model monkeys

Abstract: Central poststroke pain (CPSP) develops after a stroke around the somatosensory pathway. CPSP is hypothesized to be caused by maladaptive reorganization between various brain regions. The treatment for CPSP has not been established; however, repetitive transcranial magnetic stimulation (rTMS) to the primary motor cortex has a clinical effect. To verify the functional reorganization hypothesis for CPSP development and rTMS therapeutic mechanism, we longitudinally pursued the structural and functional changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…They suggest that central pain is due to lateral thalamus hyperexcitability, which is associated with the expressions of calcium-voltage-dependent channels and changes in the GABAergic inhibitory system. Similar results in other animal studies have shown a possible association in the development of CPSP, with increased connections in the affected hemisphere, between the mediodorsal nucleus of the thalamus and the amygdala (38). In addition, in a study by Kuan et al (39), aberrant neuronal activity in the pathway between the medial thalamus and cingulate cortex, having the brain-derived neurotrophic factor (BDNF) as a mediator, was observed.…”
Section: Physiopathology Theories and Plasticity Role In Cpspsupporting
confidence: 79%
“…They suggest that central pain is due to lateral thalamus hyperexcitability, which is associated with the expressions of calcium-voltage-dependent channels and changes in the GABAergic inhibitory system. Similar results in other animal studies have shown a possible association in the development of CPSP, with increased connections in the affected hemisphere, between the mediodorsal nucleus of the thalamus and the amygdala (38). In addition, in a study by Kuan et al (39), aberrant neuronal activity in the pathway between the medial thalamus and cingulate cortex, having the brain-derived neurotrophic factor (BDNF) as a mediator, was observed.…”
Section: Physiopathology Theories and Plasticity Role In Cpspsupporting
confidence: 79%
“…Non-human primates can be trained to sit in a monkey chair ( McMillan et al, 2014 ) and receive rTMS daily while awake ( Aceves-Serrano et al, 2019a , b ). The variety of available primate models of diseases such as Parkinson’s disease, epilepsy, and stroke can be used to provide insights into the effects of rTMS in these different disorders ( Bezard et al, 1997 ; Szabó et al, 2005 ; Kadono et al, 2021 ). Finally, healthy non-human primates could help to evaluate the impact of a clinical course of rTMS delivery and allow for comparison between the effects of rTMS in the healthy and non-healthy brain.…”
Section: Imaging Studies Of Repetitive Transcranial Magnetic Stimulat...mentioning
confidence: 99%
“…Magnetic resonance studies of rTMS effects have also been carried in animals. In a non-human primate model of post-stroke pain, fMRI evaluation demonstrated HF-rTMS over the ipsilesional motor cortex induced pain relief and changes in connectivity between the thalamus and the amygdala ( Kadono et al, 2021 ). While, in rats, a resting-state fMRI study showed different rTMS frequencies and patterns (1 Hz, 10 Hz, continuous theta-burst stimulation (cTBS) or biomimetic high-frequency stimulation) delivered over the right hemisphere modulated connectivity in the somatosensory cortex, the motor cortex, and the hippocampus ( Seewoo et al, 2018 ).…”
Section: Imaging Studies Of Repetitive Transcranial Magnetic Stimulat...mentioning
confidence: 99%
“…Evidence from animal studies suggests that CPSP reduces functional connectivity between the VPL and S1 (primary somatosensory cortex)/S2 (secondary somatosensory cortex) (responsible for perceiving pain location, intensity, and duration) and increases functional connectivity (responsible for the attentional, cognitive, and emotional aspects of pain evaluation) between the mediodorsal nucleus (Tarragó et al, 2016) and the amygdala. rTMS therapy relieves this abnormal connection (Kadono et al, 2021), so we speculate that this may be one of the mechanisms of rTMS pain relief.…”
Section: Rtms a Ects Functional Reorganization Of The Brainmentioning
confidence: 87%